Small Magellanic Cloud: Star-Formation History and X-Ray Binary Populations - Antoniou, V.; Zezas, A.; Hatzidimitriou, D.; Kalogera, V. (2010)
Using Chandra, XMM-Newton and optical photometric catalogs we study the young XRB populations of the SMC. We find that the Be-XRBs are observed in regions with star formation (SF) rate bursts ˜25-60 Myr ago. The similarity of this age with the age of maximum occurrence of the Be phenomenon (˜40 Myr) indicates that the presence of a circumstellar decretion disk plays a significant role in the number of observed XRBs in the 10-100 Myr age range. We also find that regions with strong but more recent SF (e.g. the Wing) are deficient in Be-XRBs. By correlating the number of observed Be-XRBs with the formation rate of their parent populations, we measure a Be-XRB production rate of ˜1 system per 10-6 Msun/yr. Finally, we use the strong localization of the Be-XRB systems in order to set limits on the kicks imparted on the neutron star during the supernova explosion.